Pengaruh penambahan tepung maggot black soldier fly (Hermetia illucens) dalam ransum terhadap performa produksi puyuh petelur - Ade Trisna; Muhammad Amran; Wanda Pratama (Fakultas Pertanian Universitas Majalengka, 2024)
This study aims to determined the effect of adding Black Soldier Fly (Hermetia illucens) maggot meal with fermented palm oil sludge culture media on the performance production of laying quail. This study used the experimental method and a Completely Randomized Design (CRD) with five treatments and four replications. The treatment was the replacement of fish meal with BSF maggot flour, namely: A (0% BSF maggot and 12% fish meal), B (4% BSF maggot and 9% fish meal), C (8% BSF maggot and 6% fish meal), D (12% BSF maggot and 3% fish meal) and E (16% BSF maggot and 0% fish meal). The variables observed were ration consumption, feed conversion, egg weight, and daily egg production. The results showed that each treatment had no significant effect (p>0.05) on quail's production performance. The study concludes that using 16% BSF maggot flour can replace the use of fish meal and has a good effect on the production performance of quail. Under these conditions, ration consumption was 19.34 g/head/day, daily egg production was 71.13%, feed conversion was 2.52, and egg weight was 10.82 grams/egg. The best treatment was determined based on the price of the ration. The price of the ration in treatment E, using 16% BSF maggot flour in the laying quarter ration, was IDR6,705.00 lower than that of the other treatments. We found that feeding BSF maggot flour with fermentation culture media as a protein source to replace fishmeal in the laying quail ration up to 16% can maintain the birds' production performance. Besides, the best treatment was also determined based on the lowest ration price compared to the other treatments, which was Rp6,705.00/kg.